2009
DOI: 10.1002/net.20303
|View full text |Cite
|
Sign up to set email alerts
|

Approximability of unsplittable shortest path routing problems

Abstract: In this article, we discuss the relation of unsplittable shortest path routing (USPR) to other routing schemes and study the approximability of three USPR network planning problems. Given a digraph D = (V , A) and a set K of directed commodities, an USPR is a set of flow paths P * (s,t) , (s, t) ∈ K , such that there exists a metric λ = (λ a ) ∈ Z Z Z A + with respect to which each P * (s,t) is the unique shortest (s, t)-path. In the MinCon-USPR problem, we seek an USPR that minimizes the maximum congestion ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Notable research in optimizing OSPF weights has been reported in the literature [2,4,6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The pioneering work on the OPSF weight setting problem was done by Fortz and Thorup [8,10,29] who used maximum utilization as the optimization objective.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Notable research in optimizing OSPF weights has been reported in the literature [2,4,6,[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The pioneering work on the OPSF weight setting problem was done by Fortz and Thorup [8,10,29] who used maximum utilization as the optimization objective.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These weights are in the range [1,20]. A solution for this topology can be (18,1,7,15,3,17,14,19,13,18,4,16,16).…”
Section: Open Shortest Path First Weight Setting Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem cannot be approximated within a factor of O(2 log 1−ǫ |V | ) in the directed and within a factor of 2 − ǫ in the undirected case, unless P = N P. For various special cases, however, better approximation algorithms can be derived. For the case where the underlying network is an undirected cycle or a bidirected ring, for example, Min-Con-USPR and Cap-USPR are approximable within constant factors [5].…”
Section: Hardness and Approximabilitymentioning
confidence: 99%